2015
DOI: 10.1038/srep13817
|View full text |Cite
|
Sign up to set email alerts
|

Bias field tailored plasmonic nano-electrode for high-power terahertz photonic devices

Abstract: Photoconductive antennas with nano-structured electrodes and which show significantly improved performances have been proposed to satisfy the demand for compact and efficient terahertz (THz) sources. Plasmonic field enhancement was previously considered the dominant mechanism accounting for the improvements in the underlying physics. However, we discovered that the role of plasmonic field enhancement is limited and near-field distribution of bias field should be considered as well. In this paper, we clearly sh… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
30
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 49 publications
(30 citation statements)
references
References 40 publications
0
30
0
Order By: Relevance
“…66,71,72,76,140,[163][164][165][166] The key distinction here is that, in this configuration, the nanostructured regions are electrically continuous with either the anode or cathode, rather than being electrically isolated. An example of this from the work of Moon et al 167 is shown in Fig. 14 [Fig.…”
Section: Nanostructured Electrodesmentioning
confidence: 99%
See 3 more Smart Citations
“…66,71,72,76,140,[163][164][165][166] The key distinction here is that, in this configuration, the nanostructured regions are electrically continuous with either the anode or cathode, rather than being electrically isolated. An example of this from the work of Moon et al 167 is shown in Fig. 14 [Fig.…”
Section: Nanostructured Electrodesmentioning
confidence: 99%
“…Here, a microscopic image of a standard dipole antenna structure is shown, along with SEM images of the various nanoplasmonic grating structures fabricated as part of the dipole electrodes. 167 Most work investigating nanostructured electrodes attempt to enhance the near-anode effect, the high output THz power that is observed when the optical pump is centered over the anode. By nanostructuring the antenna electrodes, the effective area of the near-anode region can be increased, so the full area of the incident optical pump falls on the nearanode region.…”
Section: Nanostructured Electrodesmentioning
confidence: 99%
See 2 more Smart Citations
“…The efficiency of photoconductive (PC) THz detectors based on low temperature grown (LT) GaAs is limited by the bulk material properties: the mean free path of photo-excited carriers, and the optical absorption length. A popular method to mitigate the material limitations is to modify the photoconductive antenna to incorporate plasmonic nano-electrodes [1][2][3][4][5][6] . These electrodes support an optical plasmon resonance, which strongly localizes the generation of electron-hole pairs to the vicinity of the nano-electrodes.…”
Section: Introductionmentioning
confidence: 99%